AmazonAfricas: literary engagement, creolization, and self-movement in Amílcar Cabral and Bruno de Menezes - Fernandes, José Guilherme dos Santos; Trusen , Sylvia Maria; Martins, Rayane Tamborini (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
This article investigates literary engagement, creolization, and self-movement in the poetics of Amílcar Cabral and Bruno de Menezes, whose trajectories are inscribed in the decolonization struggles in Cape Verde and Brazil. It begins with a comparative analysis, based on references related to the context of the study, to understand how the works of these authors express resistance to the cultural hegemony imposed by the coloniality of power. The methodology is grounded in a critical and interpretative reading of their literary productions, linked to the historical context in which colonized subjectivities were formed. It is observed that, despite being separated by distinct spatial and temporal contexts, both poets construct a poetics of confrontation with colonial structures, redefining the language of the colonizer by means of cultural and popular elements, territorial resonances, and environments touched by the decolonial struggle, whether in the urban periphery of the Amazon in Pará or in the torrid island landscapes of Cape Verde. It is concluded that Cabral and Menezes’ engaged literature operates as aesthetic and political praxis, promoting the symbolic reterritorialization of subalternized identities and the emergence of a diverse poetics, affirmed in the continuous creation and reinvention of the historical experience of exiled peoples.